OPTIMALISASI PENGGUNAAN LAHAN UNTUK TANAMAN JERUK BESAR (Citrus maxima Merr.) BERBASIS EVALUASI LAHAN DAN KELAYAKAN EKONOMI DI KECAMATAN LABAKKANG KABUPATEN PANGKEP - Karmiati Karmiati; Amir Tjoneng; Edy Edy (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
The purpose of this study were: 1) determine the suitability of land for large citrus plants in Labakkang District, Pangkep Regency, 2) determine the limiting factors of large citrus plants, 3) analyze the improvement of land for large citrus plants, 4) analyze the economic feasibility of citrus farming big, 5) determine the optimization of the use of large citrus farming land in Labakkang sub-district, Pangkep district. This research was carried out in Labakkang District, Pangkep Regency. Analysis of soil samples was carried out at the Laboratory of Chemistry and Soil Fertility at the Department of Soil Science, Faculty of Agriculture, Hasanuddin University. Land suitability analysis and land suitability criteria based on FAO (1976). The research phase includes the preparation stage, map making, soil sampling and interviews, analysis of soil samples in the laboratory, land suitability analysis and farming analysis. The results showed that the actual land suitability class in the study area was class N2 found in land unit 1, class S2 was on land unit 2,3,4,5,6,7. The dominant limiting factors are water availability, rooting media, available nutrients and erosion hazard level. Grapefruit has an opportunity to be cultivated as indicated by the R / C ratio of 1.72 which means it is beneficial for farmers. Land use obtained from the highest land evaluation with the level of economic income was obtained in the village of Kassilowe with the highest income of a farmer of Rp. 13,000,000 and found in the suitability of potential land for S2r.